1999
DOI: 10.1038/sj.bjc.6690164
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine RANTES is secreted by human melanoma cells and is associated with enhanced tumour formation in nude mice

Abstract: Modulation of tumour cell growth by tumour-infiltrating leucocytes is of high importance for the biological behaviour of malignant neoplasms. In melanoma, tumour-associated macrophages (TAM) and tumour-infiltrating lymphocytes (TIL) are of particular interest as inhibitors or enhancers of cell growth. Recruitment of leucocytes from the peripheral blood into the tumour site is mediated predominantly by chemotaxins, particularly by the group of chemokines. The aim of this study was to identify peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 26 publications
2
81
0
3
Order By: Relevance
“…Invasive melanoma is highly resistant to standard forms of cancer therapy (for a review, see Ueda and Richmond, 2006). Based on the fact that several NF-kB-regulated chemokines are constitutively expressed in human melanoma (Mrowietz et al, 1999;Singh et al, 1999;Ueda and Richmond, 2006), it has been proposed that NF-kB plays an important role in melanoma. The role for these chemokines is thought to be at the level of enhancement of growth and survival through autocrine and paracrine mechanisms.…”
Section: Melanoma and Nf-kbmentioning
confidence: 99%
“…Invasive melanoma is highly resistant to standard forms of cancer therapy (for a review, see Ueda and Richmond, 2006). Based on the fact that several NF-kB-regulated chemokines are constitutively expressed in human melanoma (Mrowietz et al, 1999;Singh et al, 1999;Ueda and Richmond, 2006), it has been proposed that NF-kB plays an important role in melanoma. The role for these chemokines is thought to be at the level of enhancement of growth and survival through autocrine and paracrine mechanisms.…”
Section: Melanoma and Nf-kbmentioning
confidence: 99%
“…70 There is evidence that inflammatory chemokines including CCL5 expressed by prostate cells may act directly on the growth and survival of hormone-driven prostate cancer cells. 75 In a Japanese study, it was found that serum CCL5 concentration was significantly elevated in the ovarian cancer patients compared to the benign ovarian cyst patients as controls correlating with the stage of disease and the extent of residual tumor mass.…”
Section: Ccl5 and Other Cancersmentioning
confidence: 99%
“…A number of other cancer types have been shown to express CCL5, [70][71][72][73][74] induce inflammatory cell migration into the tumor site 71,73,74 and enhance tumor growth. 70 There is evidence that inflammatory chemokines including CCL5 expressed by prostate cells may act directly on the growth and survival of hormone-driven prostate cancer cells.…”
Section: Ccl5 and Other Cancersmentioning
confidence: 99%
“…In terms of breast cancer, a number of studies have suggested that RANTES is associated with breast malignancy. In patients with breast cancer, advanced disease, early relapse, and poor prognosis are significantly correlated with elevated RANTES expression levels in biopsy specimens and serum (26)(27)(28). Therefore, the precise role of RANTES signaling in breast cancer should be clarified.…”
Section: Introductionmentioning
confidence: 99%